THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING MOVIES USING ENGLISH SUBTITLES AND THEIR VOCABULARY MASTERY AT ENGLISH DEPARTMENT UNIVERSITAS ISLAM MALANG - Yunita Safitri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The aims of the research were to find out whether or not there is any significant correlation between students’ habits in watching movies using English subtitles and vocabulary mastery at the English Department Unisma. The research design was the quantitative method. In collecting the data, the researcher used a questionnaire and test. The population of the study was the eight-semester students of the English Department Unisma. The sample of the study consisted of 37 students. To analyze the data, the researcher used SPSS 26.0. The research findings show that there is any correlation but insignificant between students’ habit in watching movies using English subtitle and vocabulary mastery (rxy = 0.155≤rtable = 0.325). So, the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. The meaning of this statement is the students’ habit in watching movies using English subtitles has a relationship but is insignificant to students’ vocabulary mastery. On the finding of the study, it is addressed to English students to apply this strategies to improve their vocabulary mastery. For the next researchers are expected to investigate other skills and components of English and explore knowledge in order to give more benefit to the result and by involving more participants. keywords: Correlation, watching movies using English subtitles, vocabulary mastery.